Evaluating the need for recovery from work for site-based construction practitioners in Australia. Issue 3 (1st November 2022) - Sun, C; Hon, C K H; Jimmieson, N L; Way, K A; Xia, B
Abstract: Site-based construction practitioners face high levels of job stress and need to recuperate from work-induced fatigue. Insufficient recovery from work will lead to work fatigue and health problems. While need for recovery (NFR) is an important concept to the wellbeing of construction practitioners, there is limited study in this area. Thus, this study aims to evaluate NFR for site-based construction practitioners in Australia and identify patterns of NFR as a function of demographics and work characteristics. A survey was conducted with site-based construction practitioners in Australia. Descriptive statistics, correlation analysis, and analysis of variance (ANOVA) were employed to analyse collected data. Results showed that the mean NFR of site-based construction practitioners in Australia was 17.96 (range = 6 – 30, 6 items). Age and work hours explained differences in NFR mean scores according to both the one-way ANOVA and correlations. NFR increased with work hours and decreased with age, with r = 0.19 and r = -0.24 respectively. The correlation analysis also indicated the negative relationship between work experience and NFR ( r = -0.21). Work experience and work hours interacted to influence NFR according to the two-way ANOVA. The positive relationship between work hours (≤ 60 hours) and NFR was weaker in those with more work experience while this moderating effect of work experience did not apply to people working more than 60 hours. The significance of the study lies in providing insights to increase the work capacity of construction practitioners and help them to recover from job stress.